Evidence of a hierarchical representation in bodily self-consciousness: the neural correlates of embodiment and presence in virtual worlds - Owens, Evan Alexander; Duncan, Robert O. (Frontiers in Human Neuroscience, 2025)
IntroductionBodily Self-Consciousness (BSC) is the perception of bodily awareness that arises from the integration of neuronal signals in multiple sensory modalities. BSC is composed of embodiment (the perception of owning a body) and presence (the perception of being at a location). Converging lines of evidence suggest embodiment and presence are supported by different neural networks. Several models have been proposed to describe how BSC manifests from these networks, but how these networks interact is not fully understood. We propose that the perception of presence is predicated upon the perception of embodiment. Specifically, even though neural networks for presence and embodiment partially overlap, there exists a subset of brain areas that mediate the flow of information from those supporting embodiment to those supporting presence.MethodsTo test this model, sensory feedback was manipulated in a virtual environment to affect BSC, while measuring behavioral performance and physiological responses in relevant brain areas. Correlated versus uncorrelated feedback was used to manipulate perceptions of embodiment. First- versus third-person perspective was used to manipulate perceptions of presence.ResultsMean reaction times and accuracy were better with correlated feedback and first-person perspective. Functional magnetic resonance imaging (fMRI) measurements of neuronal activity identified frontoparietal and temporoparietal brain areas that appear to support embodiment and presence, respectively. We compared the effect of embodiment manipulations on presence areas and vice versa. The effect sizes for manipulations of embodiment were greater than those for manipulations of presence. This trend was also observed for brain areas that appeared to encode both embodiment and presence.DiscussionThis data indicates that networks associated with embodiment and presence overlap, and brain areas that support presence may depend upon the activity of those that support embodiment.